Hydromagnetic flow past an exponentially accelerated isothermal vertical plate with uniform mass diffusion in the presence of chemical reaction of first order - Muthucumaraswamy, Rajamanickam; Valliammal, V. (Zielona Góra: Uniwersytet Zielonogórski)
An exact solution of an unsteady flow past an exponentially accelerated infinite isothermal vertical plate with uniform mass diffusion in the presence of a transverse magnetic field has been studied. The plate temperature is raised to Tw and the species concentration level near the plate is also made to rise C`w. The dimensionless governing equations are solved using the Laplace-transform technique. The velocity, temperature and concentration profiles are studied for different physical parameters such as the magnetic field parameter, chemical reaction parameter, thermal Grashof number, mass Grashof number, Schmidt number, time and a. It is observed that the velocity decreases with increasing the magnetic field parameter.
Keywords: accelerated; isothermal; vertical plate; exponential; heat transfer; mass transfer; chemical reaction; magnetic field